Marriage Age Limit In Hanafi Mazhab And Its Relevance With Law No. 16 Years 2019 - Abdul Hamid; Ahmad Maulidin (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2022)
The priests of the madhhab did not mention the age limit for marriage, but only set the age of puberty. Whereas in the compilation of Islamic law and the Act there is a provision which states that the age limit for marriage is Law No. 1 of 1974 for women at least 16 years, for men 19 years, then revised by Law No. 16 of 2019 that men and women must be at least 19 years old. year. Thus the author wants to find the relevance of the provisions on the age limit for marriage contained in the law and the opinions of the Hanafi school. This is postulated in a hadith narrated by Imam Bukhari from Sayyidah Aisyah ra. In this study, we want to examine how the comparison of underage marriage between the Hanafi school and Law no. 16 of 2019. This type of research is library research with a juridical-normative approach. The results of this study conclude that underage marriage is not allowed in Law no. 16 of 2019 because it raises many negative elements from positive things. While in the Hanafi school there is no prohibition against underage marriage as long as it does not cause negative effects.